Yearbook of Private International Law. - Bonomi, Andrea; Romano, Gian Paolo (Yearbook of Privat International Law ;, 2013)
The "Yearbook of Private International Law" provides all about the conflict of laws developments of 2012 and 2013 in one book: Volume XIV (2012/2013) includes contributions on the proposed codification of the General Part of Private International Law in Europe, on the reform of the Chinese legal system as well as on defamation and violation of personality rights (the latter in a whole section). Furthermore, the book deals with the application of EU legislation on jurisdiction and enforcement of judgements, the recognition of judgements overturned by another judgement, and the conflict of decisions in international arbitration. Reports and court decisions from the Netherlands, Turkey, India, Finland, Croatia and Switzerland and a summary of two dissertations on the role of sovereignty and choice of courts agreements complete the book.